On Reducing Intercept Probability for Unsubscribed Video Layers Using Network Coding - Karim, Mohammad S.; Esmaeilzadeh, Mohammad; Sadeghi, Parastoo (IEEE communications letters, 2017)
In this letter, we use random linear network coding (RLNC) to deliver a two layered video sequence to two wireless subscribers such that a high-paying subscriber receives the highest quality and a low-paying subscriber receives the basic quality. We first derive closed-form expressions for the probability of the low-paying subscriber intercepting sufficient coded packets to experience the highest video quality. We consider both feedback-aided and feedback-free transmissions. We propose a resource allocation framework that minimizes the intercept probability subject to deadline and subscribed video quality constraints. We show the tightness between the theoretical and simulation results, and illustrate the protection achieved by RLNC for subscription-based layered video delivery.